Pelatihan Pembuatan Granul Herbal Daun Jambu Biji sebagai Upaya Pemanfaatan Tanaman Obat Keluarga - Khandela Pasha; Marlina Indriastuti; Adinda Esya Nurkirani; Nuni Sakinatun Nisa; Risna Putri Dwijayanti; Sintia Wati; Sofiah Nur Syaida Rangkuti (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Guava leaves (Psidium guajava L.) are one of the herbal plants widely used by the community to help manage diarrhea. However, their utilization is still limited to simple decoctions, which are less practical and have low stability. Objective: This community service activity aimed to improve community knowledge and skills in processing guava leaves into a herbal granule preparation that is more practical, stable, and easy to use. Method: The methods used included educational counseling and hands-on practice in granule preparation using the wet granulation technique. The activity was conducted in Sukaraja Village and involved members of the PKK women’s group as the main participants. Result: The activity improved participants’ knowledge regarding the benefits of guava leaves and enhanced their skills in preparing herbal granules. The resulting granules exhibited good physical characteristics, were easily soluble, and had an infusion pH within a safe range. Conclusion: This mentoring program was effective in enhancing the community’s ability to utilize local herbal plants in a simple and appropriate manner.